Pengenalan PhET Simulations Sebagai Laboratorium Virtual Untuk Membantu Pemahaman Konsep Fisika Materi Kesetimbangan Pada Peserta Didik Kelas 8 SMP 06 Diponegoro - Albis, M. Miftu Khurizil; Ni’mah, Simatun; Adilah, Bilqis (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
PhET Simulation is a virtual lab that can be used as a learning medium for science material. Apart from that, PhET Simulation can also be used as an alternative medium for practical activities. This service activity aims to introduce PhET Simulation as a virtual laboratory to students in class 06 Diponegoro Middle School and help students understand equilibrium material in physics lessons. This service activity was held on Tuesday, October 3 2023 at SMP 06 Diponegoro, which was attended by 30 students from class VIII. The introduction of PhET Simulation activities took place in the science laboratory room at SMP 06 Diponegoro. This service method begins with an explanation of PhET Simulation and the use of PhET Simulation in equilibrium material, questions and answers regarding PhET Simulation, and ends with students practicing using PhET Simulation. It is hoped that this service activity can help students understand equilibrium physics material in class VIII SMP 06 Diponegoro in 2023.